Words, Pictures, and Arguments: A Relevance-Theoretic Synthesis - Gerald Delahunty (Journal of Linguistics and Language Teaching)
Whether visual representation can function in arguments is a controversial issue. Those who claim they cannot, claim that only propositions may function thus and that as visuals cannot represent propositions, they cannot function in arguments. The current paper, invoking recent developments in Relevance Theory, demonstrates that visuals, specifically photographs, can represent propositions and can therefore function as and in arguments. The paper demonstrates that visuals also communicate more than propositions in that they provide evidence for a range of ‘impressions’ that support a ‘credal attitude’ toward the document in which they occur.